Psychological challenges faced by multidrug-resistant tuberculosis patients: a systematic review - Qanita Syakiratin; Adik Wibowo; Esty Febriani (Berita Kedokteran Masyarakat (BKM), 2019)
Purpose: Multidrug-resistant tuberculosis (MDR-TB) patients have few adverse effects due to treatment regimens, including psychological side effects that play an important role in the successful MDR-TB management. This study was aimed to identify MDR-TB patients’ challenges within the context of psychological issues and to determine suitable intervention to address psychological problems in MDR-TB patients.Method: We conducted a systematic review as PRISMA guidelines using databases PubMed, ProQuest, ScienceDirect, Scopus, and Portal Garuda to search for all related articles. From studies identified, 10 were included in the final analysis.Results: It was found that all studies have documented a range of psychological challenges faced by MDR-TB patients that were depression, anxiety, suicidal tendencies and common issues reported in the studies.Conclusion: Three main strategies can be implemented in every country to address MDR-TB adverse effects and scale-up MDR-TB treatment efficacy. These strategies require high levels of support from health workers and family member which has an important role in the treatment process.